Ant and spider species as surrogates for functional community composition of epiphyte-associated invertebrates in a tropical moist forest. (January 2019) - Céréghino, Régis; Corbara, Bruno; Hénaut, Yann; Bonhomme, Camille; Compin, Arthur; Dejean, Alain
Highlights: Tank bromeliads host diverse aquatic invertebrate communities in tropical forests. Bromeliad features determine the functional trait composition of invertebrates. Indicator ants and spiders predict aquatic invertebrate traits in tank bromeliads. Surrogate species indicate pelagic, benthic and interstitial food webs in bromeliads. Abstract: Epiphytes represent up to 50% of all plant species in rainforests, where they host a substantial amount of invertebrate biomass. Efficient surrogates for epiphyte invertebrate communities could reduce the cost of biomonitoring surveys while preventing destructive sampling of the plants. Here, we focus on the invertebrate communities associated to tank bromeliads. We ask whether the presence of particular ant and/or spider taxa (easily surveyed taxa) that use these plants as nesting and/or foraging habitats predicts functional trait combinations of aquatic invertebrate communities hosted by the plants. Functional community composition of invertebrates was predicted both by bromeliad habitat features and the presence of certain ant and spider species. The ant Azteca serica preferred wider bromeliad rosettes that trap large amount of detritus, indicating interstitial-like food webs dominated by deposit feeders that burrow in fine particulate organic matter. Leucauge sp. spiders preferred narrower bromeliad rosettes bearing smaller detrital loads, thereby indicating a dominance of pelagic filter-feeding and predatory invertebrates in the water-filled leaf axils. Both Neoponera villosa ants and Eriophora sp. spiders preferred rosettes at intermediate size bearing moderate amounts of detritus, indicating a benthic food web dominated by leaf shredders and gathering collectors. Owing to the animal diversity and biomass supported by rainforest epiphytes, our approach would deserve to be further tested on a range of epiphytes involved in tight interactions with invertebrates. In this context, surrogate species could serve both as indicators of functional diversity, and as early-warning indicators of network disassembly.